Additional role of ECC in the detection and treatment of cervical HSIL - Sijing, Li; Ying, Jia; Jing, Wu; Xiaoge, Li; Ming, Luo; Zhaoning, Duan (Frontiers in Medicine, 2023)
Objective: To probe into the additional role of ECC in the detection of cervical HSIL. The primary objective was to risk-stratify HSIL patients according to ECC so as to provide clinical suggestions for subsequent treatment. Methods: Retrospective analysis of medical records for patients with HSIL. All patients underwent both ECC and cervical biopsy. According to the results of colposcopic targeted biopsy and ECC, the patients were divided into three groups: (1) ECC negative group (those whose colposcopic targeted biopsy indicated HSIL, but ECC indicated LSIL or chronic inflammation); (2) Only the ECC positive group (those whose ECC suggested HSIL, but colposcopic targeted biopsy showed LSIL or chronic inflammation); (3) ECC and biopsy positive group (those whose ECC and targeted biopsy were both HSIL). Chi-square test was used to analyze the differences of lesion residue and biopsy results after LEEP amongst the three groups. Results: A total of 1146 medical records were analyzed. The diagnostic accuracy of ECC combined with colposcopic targeted biopsy for HSIL was higher than that of colposcopic biopsy alone (72.43% vs 67.54%). When ECC indicated HSIL, the coincidence rate of ECC combined with colposcopic targeted biopsy and the histological pathology of LEEP was 86.25%, and the proportion of residual lesions after LEEP was 41.43%. When ECC and targeted biopsy both indicated HSIL, HSIL or worse lesions were confirmed in 90.68% of patients after surgery. Of these, 10.77% were confirmed as cervical invasive carcinoma. Moreover, the positive rate of LEEP resection margin and postoperative ECC in these patients was 43.48%. Conclusion: ECC can improve the detection rate of cervical HSIL and reduce missed diagnosis. Also ECC can help clinicians predict the proportion of residual lesions after LEEP. This provides the gynecologists with a reference for the need to increase the depth of the procedure and the need to perform ECC for the residual cervical canal.